Human histocompatibility antigen associations in subacute cutaneous lupus erythematosus. - Sontheimer, R D (1981)
We have identified a clinically distinct subset of lupus erythematosus patients marked by the presence of a histologically proven, nonscarring variety of cutaneous LE (subacute cutaneous LE) in which there is a very high frequency of the human leukocyte antigens (HLA) B8 and DR3. Differences in the configuration of their skin lesions allowed a separation of the patients into two clinical subgroups; annular and papulosquamous. HLA-B8 was increased in the annular subgroup (81%, corrected P (Pc) < 0.007) and combined group (65%, Pc < 0.004). HLA-DR3 was present in all 11 of the annular patients (10%, Pc < 0.00008). In addition, HLA-DR3 was present in increased frequencies in the papulosquamous subgroup (60%, Pc < 0.04) and combined group (77%, Pc < 0.00008). Thus, HLA-DR3 positive individuals have a relative risk of 10.8 for developing subacute cutaneous LE of either type and an even greater relative risk (67.1) for the annular variety. The HLA phenotype A1, B8, DR3 was also found more commonly in the annular (73%, P < 0.00008) and combined patient groups (46%, P < 0.004). These HLA associations, which are stronger than ever before reported for any form of LE, did not result from the concurrent presence of subclinical Sjögren's syndrome. Thus, subacute cutaneous LE can now be added to the growing list of HLA-B8, DR3-associated diseases that have autoimmune features.